Agency relationship in Global Venture Lab - Oksanen, Mikko (2014)
This Master's thesis analyzes the Agency relationships in university environment by applying a Global Venture Lab model of organization. The Global Venture Lab described in this study is a growth venture incubator that has been developed in the private organizational model to supplement the general faculty governance and the development of the University in the field of commercialization of inventions. In the study, the agent theory dimensions of moral hazard and adverse selection are applied. The research is conducted by action research methods and it is partly written in real time and partly with a retrospective approach. The data of the research is gathered during the development project of Global Venture Lab in years 2008 to 2011. During the research work, the Runway to Growth program was developed and the lessons learned from combining different fields of expertise are applied. In the research it is established that there exists a need for applying the Agency theory in the university context in general, and that the private faculty structure may offer some improvements for Agency theory related problems. During the research process a detailed description of Global Venture Lab was built, as well as an application of funnel model for students’ engagement to real life business development projects.